Factors associated with guideline‐based hepatitis C virus (HCV) treatment initiation in HIV/HCV‐coinfected patients: role of comorbidities and physicians' perceptions. Issue 7 (5th March 2013) - Winnock, M; Bani‐Sadr, F; Pambrun, E; Loko, M‐A; Carrieri, P; Neau, D; Morlat, P; Marchou, B; Dabis, F; Salmon, D; ,
<x xml:space="preserve">Abstract</x> Objectives Many HIV‐infected patients with chronic hepatitis C virus (HCV) infection do not receive treatment for HCV infection, often because of contraindications or poor adherence to anti‐HIV therapy. The aim of this study was to identify factors influencing guideline‐based HCV treatment initiation in a large cohort of HIV/HCV‐coinfected patients. Methods Between 2005 and 2011, 194 (40.5%) of 479 coinfected patients not previously treated for HCV infection started this treatment based on current recommendations, i.e. a Metavir score > F1 for liver fibrosis; HCV genotype 2 or 3 infection; or HCV genotype 1 or 4 infection and low HCV viral load (< 800 000 IU/mL), whatever the fibrosis score. Clinical and biological data were compared between patients who started HCV therapy during follow‐up and those who did not. Results In multivariate analyses, good adherence to treatment for HIV infection, as judged by the patient's physician, was associated with HCV treatment initiation [odds ratio (OR) 2.37; 95% confidence interval (CI) 1.17–4.81; P = 0.017], whereas patients with children (OR 0.53; 95% CI 0.30–0.91; P = 0.022) and those with cardiovascular disease or respiratory distress (OR 0.10; 95% CI 0.01–0.78; P = 0.03) were less likely to be treated. Conclusions Adherence to treatment for HIV infection, as judged by the patient's physician, appears to have a major influence on the decision to begin treatment for HCV infection in coinfected patients. This calls for specific therapeutic education and adherence support in order to ensure timely anti‐HCV therapy in this population.